A Rational Method ( Modified Stewart ) for Spacing Builds and Trenches Across Slope and Spacing of Graded Trenches at Ootacamund - Das, D.C.; Raghunath, B.; Pooranchandra, G. (Journal of Soil and Water Conservation, 2022)
A land treatment across the slope taken here as any physical measure used to break the slope length for reducing run-off and soil loss hazards and for conserving soil moisture on land. The basis, that will be discussed here under, will be applicable to all types of terracing and trenching, except bench terracing, where depth of cut available is a predominant factor in the designing. Presently the spacing of such mechanical measures are done empirically and its effectiveness depends much on personal judgment. In this region, for slopes ranging from 10% to 16% graded trenches are recommended. No data are available to ascertain the best spacing for such trenches or to provide a basis for determining such spacings.